Expectant /conservative management of severe preeclampsia far from term - Vigil-De Gracia, Paulino (2015)
Severe preeclampsia that develops at <34 weeks of gestation is associated with high perinatalmortality and morbidity rates. Management with immediate delivery leads to high neonatalmortality and morbidity rates and prolonged hospitalization in the neonatal intensivecare unit because of prematurity. Conversely, attempts to prolong pregnancy with expectantmanagement may result in fetal death or asphyxia damage in utero and increased maternalmorbidity. Expectant care has been compared with interventionist care in three randomizedcontrolled trials (RCTs) that enrolled 400 women. Interventionist care was associated withmore respiratory distress syndrome but similar neonatal intensive care unit (NICU) admissionand neonatal mortality. Expectant care was associated with a mean pregnancy prolongationof 1-2 weeks, but more small for gestational age (SGA) infants and abruptio placentae. Womenwith severe preeclampsia before 34 weeks may benefit from stabilization on a 48-72 hourperiod, to enable maximal effect of antenatal corticosteroids and delivery. Women with severepreeclampsia between 24-28 weeks may benefit from effect of antenatal corticosteroidsand observation with possible expectant management and delivery due to maternal o fetalconditions.Keywords: Expectant management, severe preeclampsia at <34 weeks of gestation, eclampsia,perinatal mortality.